Hur bra är dagens rekommendationer för markkartering? - Ringdahl, Fabian (2018)
For a long time in Sweden, there has been a general practice to perform soil mapping as a basis for manure and lime distribution. The recommendations currently available for how often soil mapping should be performed consist of basic mapping for clay content, organic carbon content, P-AL, K-AL and pH. After that a follow-up action is performed approximately every ten years. There is a lack of support for how often a soil mapping needs to be established and according to the literature that has been studied, no studies have been made concerning observed changes of phosphorus content in soil mapping over time. In the present study, eight Swedish farms were included. Soil maps from two different occasions performed on the farms have been compared to evaluate how the amount of AL-extractable phosphorus in soil changed during the period between the soil mappings. Results showed that changes in P content between the occasions could be detected, where an average of about 35 % of the area had an increase in P-AL by more than 20 % and about 14 % of the area had a decrease in P-AL by more than -20 %. However, large differences were found between farms, and on some farms, the phosphorus content had increased in almost the entire area, compared with others were the content had decreased in the majority of the area. Statistical analyses of the changes in P-AL was performed in order to investigate whether it was possible to correlate clay content, organic carbon content, initial P-AL and initial pH with changes of P-AL between the two occasions. It was found that primarily the initial PAL was correlated with the size of the change where lower P-AL values led to a greater positive change and a high P-AL value to major negative changes. For the farms, phosphorus balances were also conducted at field level to compare these with the changes in phosphorus content in the soil maps. Some of the changes can be linked to the fact that phosphorous fertilizer has been spread in order to rise the phosphorus level, but some changes are difficult to explain. One trend shown is that changes are not as expected with respect to the long-term fertility trials, especially when high amounts of phosphorus are applied. Phosphorus balances showed that most farms should have had a general decrease in P-AL values, but that was not the case. Further studies should be done on for how long time high phosphorus applications are able to deliver phosphorus and how close a soil mapping can be established after a high phosphorus application. In order to avoid variations of P-AL values in soil mapping due to high phosphorus applications and in order to see trends of how phosphorus status changes, an alternative would be to change the recommendations so that soil mapping is performed as part of the plant sequence.